2017
DOI: 10.3390/rs9070760
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Development Pattern in Beijing-Tianjin-Hebei Urban Agglomeration Using DMSP/OLS Nighttime Light Data

Abstract: Spatial inequality of urban development may cause problems like inequality of living conditions and the lack of sustainability, drawing increasing academic interests and societal concerns. Previous studies based on statistical data can hardly reveal the interior mechanism of spatial inequality due to the limitation of statistical units, while the application of remote sensing data, such as nighttime light (NTL) data, provides an effective solution. In this study, based on the DMSP/OLS NTL data, the urbanizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…To address inconsistencies among image datasets, Landsat TM images were geo-rectified against the Landsat OLI images, and then all images were projected onto the Albers equal-area conic coordinate system to accurately The area has fertile land, being one of three world-famous black soil belts, and is the main grain-producing area in China, so the area is vital for the country's food security. However, many studies have demonstrated that urban land has encroached considerably on farmland [23,32], threatening agricultural productivity in China [36]. The 40 prefecture-level cities are governed within the study area.…”
Section: Data Sources and Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…To address inconsistencies among image datasets, Landsat TM images were geo-rectified against the Landsat OLI images, and then all images were projected onto the Albers equal-area conic coordinate system to accurately The area has fertile land, being one of three world-famous black soil belts, and is the main grain-producing area in China, so the area is vital for the country's food security. However, many studies have demonstrated that urban land has encroached considerably on farmland [23,32], threatening agricultural productivity in China [36]. The 40 prefecture-level cities are governed within the study area.…”
Section: Data Sources and Preprocessingmentioning
confidence: 99%
“…However, many studies have demonstrated that urban land has encroached considerably on farmland [23,32], threatening agricultural productivity in China [36]. The 40 prefecture-level cities are governed within the study area.…”
Section: Introductionmentioning
confidence: 99%
“…The December night-time light data can reflect the final expansion of urban built-up areas and population distribution in 2013. Compared to another commonly-used stable night-time light dataset, the DMSP-OLS [35][36][37], the NPP-VIIRS DNB composite imagery has been calibrated in orbit, providing a higher spatial accuracy and solving the brightness saturation problem [34,38]. However, these data contain not only the brightness from urban areas but also abnormal values such as fire points, volcanoes and background noise.…”
Section: Datamentioning
confidence: 99%
“…To date, scholars have carried out a lot of research based on DMSP/OLS data, mainly in urban expansion [54][55][56], saturation method research [57][58][59], gross domestic product (GDP) estimation [60][61][62], carbon emissions [63][64][65], and power consumption estimation [66][67][68]. In addition, the existing research that applies DMSP/OLS data to describe the evolution of urban land use is mainly based on China at the national level [69,70] and the Beijing-Tianjin-Hebei urban agglomeration [71,72].…”
Section: Introductionmentioning
confidence: 99%